ANALYSIS OF THE CORRELATIONS BETWEEN REORDER POINT AND SAFETY STOCK IN PACKING SECTOR (CASE STUDY: PT BENTOEL Tbk.) - Guido Adriel Setiadi; Regina Odilia Rusdi; Liem Gai Sin (Journal of International Conference Proceedings (JICP), 2018)
The key of the distribution is the availability of the product and the way to manage the stock in the storage. Material’s availability is essentials to manage the flow of production within the company so they could formulated the best approach to make their production more effective and efficient that could impact the overall pricing.The purpose of this study was toconduct if the safety stock is determine how firm taking decision about reorder point in PT BentoelTbk.To collect the informatioan and data related to the topic, authors will use a method such as interview and seacrching through internet then analyzed by quantitative descriptive tecniques. Keywords:Distribution, Safety Stock, Bentoel, Reorder Point, Material’s Availability